2012
DOI: 10.1038/cr.2012.151
|View full text |Cite
|
Sign up to set email alerts
|

The novel quantitative trait locus GL3.1 controls rice grain size and yield by regulating Cyclin-T1;3

Abstract: Increased crop yields are required to support rapid population growth worldwide. Grain weight is a key component of rice yield, but the underlying molecular mechanisms that control it remain elusive. Here, we report the cloning and characterization of a new quantitative trait locus (QTL) for the control of rice grain length, weight and yield. This locus, GL3.1, encodes a protein phosphatase kelch (PPKL) family -Ser/Thr phosphatase. GL3.1 is a member of the large grain WY3 variety, which is associated with weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
279
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 388 publications
(290 citation statements)
references
References 56 publications
6
279
1
4
Order By: Relevance
“…Multiple QTLs and genes controlling rice grain size have been mapped on the 12 chromosomes using molecular markers and different mapping populations (Huang et al, 2013). Several genes controlling grain size have been analyzed (Zuo and Li, 2014), for example, GS5 , GS3 (Fan et al, 2006;Mao et al, 2010), GW2 (Song et al, 2007), GW5 (Weng et al, 2008), qSW5 (Shomura et al, 2008), qGL3 (Hu et al, 2012;Qi et al, 2012;Zhang et al, 2012), GW8 and TGW6 (Ishimaru et al, 2013), and qGL7 and GS7 (Bai et al, 2010;Shao et al, 2012). Although a number of genes for grain size have been cloned, the underlying molecular mechanisms and the potential interaction of these genes in grain size regulation remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple QTLs and genes controlling rice grain size have been mapped on the 12 chromosomes using molecular markers and different mapping populations (Huang et al, 2013). Several genes controlling grain size have been analyzed (Zuo and Li, 2014), for example, GS5 , GS3 (Fan et al, 2006;Mao et al, 2010), GW2 (Song et al, 2007), GW5 (Weng et al, 2008), qSW5 (Shomura et al, 2008), qGL3 (Hu et al, 2012;Qi et al, 2012;Zhang et al, 2012), GW8 and TGW6 (Ishimaru et al, 2013), and qGL7 and GS7 (Bai et al, 2010;Shao et al, 2012). Although a number of genes for grain size have been cloned, the underlying molecular mechanisms and the potential interaction of these genes in grain size regulation remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…GL3.1/qGL3 encodes Ser/Thr phosphatase of phosphatase kelch family to regulate grain length and yield. GL3.1/qGL3 directly down-regulates Cyclin-T1;3 to dephosphorylate Cyclin-T1;3 and results in short grain shape [43,44]. THOUSAND-GRAIN WEIGHT 6 (TGW6) controls grain length and weight, which expression is especially high around the endosperm in the pericarp.…”
Section: Qtls/genes Controlling Grain Weightmentioning
confidence: 99%
“…GS3, GL3.1/qGL3 and TGW6, three major QTLs controlling grain length, are map-based cloned and functionally analyzed [42][43][44][45]. GS3 encodes a putative trans-membrane protein containing four putative domains, a plant-specific organ size regulation (OSR) domain, a trans-membrane domain, a tumor necrosis factor receptor/nerve growth factor receptor (TNFR/NGFR) family cysteinerich domain and a von Willebrand factor type C (VWFC).…”
Section: Qtls/genes Controlling Grain Weightmentioning
confidence: 99%
“…A comparison of functional and nonfunctional sequences revealed a single nucleotide substitution (C→A) at position 1092 in exon 10, resulting in the replacement of Asp (D) (a non-functional allele) with Glu (E) (a functional allele) at the 364th amino acid. qGL3/qGL3.1 encodes a putative protein phosphatase with a Kelch-like repeat domain (OsPPKL1), which directly dephosphorylates its substrate (CyclinT1,3) to regulate cell division (Qi et al, 2012). Furthermore, genetic and transgenic studies revealed that qGL3/qGL3.1 acts as a negative regulator of grain length.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several key genes that regulate grain shape were identified (Fan et al, 2006;Shomura et al, 2008;Weng et al, 2008;Li et al, 2011;Zhang et al, 2012;Ishimaru et al, 2013;Song et al, 2007Song et al, , 2015Wang et al, 2012Wang et al, , 2015a. For instance, qGL3/qGL3.1 is a newly identified QTL associated with grain length, which exhibited the highest logarithm of the odds value and the greatest phenotypic variation compared to other markers, and it also significantly contributed to grain thickness and grain width (Hu et al, 2012;Qi et al, 2012;Zhang et al, 2012). A comparison of functional and nonfunctional sequences revealed a single nucleotide substitution (C→A) at position 1092 in exon 10, resulting in the replacement of Asp (D) (a non-functional allele) with Glu (E) (a functional allele) at the 364th amino acid.…”
Section: Introductionmentioning
confidence: 99%